Intractable convulaions in the pediatric emerency department - Osama Mohamed Mostafa Sharaf Eldin; Eman Fawzy Halawa; Eman Hassan Draz; Hala Fouad (Cairo : Osama Mohamed Mostafa Sharaf Eldin, 2013)
Background : Intractable convulsions is a medical emergency with significant associated morbidity and mortality. Aim of the work: This study was conducted to determine the etiology and outcome of intractable convulsions in children and factors related to poor outcome . Conclusion : Poor outcome was most common among infants (younger age) more common among males than females most common among patients who didn't suffer from disturbed conscious level, and mostly associated with generalized tonic clonic convusions
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Alkaline phosphatase; Creatine kinase; Reactive protein